PhoB activation in non-limiting phosphate condition by the maintenance of high polyphosphate levels in the stationary phase inhibits biofilm formation in Escherichia coli - Grillo Puertas, Mariana (2016)
Polyphosphate (polyP) degradation in Escherichia coli stationary phase triggers biofilm formation via the LuxS quorum sensing system. In media containing excess of phosphate (Pi), high polyP levels are maintained in the stationary phase with the consequent inhibition of biofilm formation. The transcriptional-response regulator PhoB, which is activated under Pi limitation, is involved in the inhibition of biofilm formation in several bacterial species. In the current study, we report, for the first time, we believe that E. coli PhoB can be activated in non-limiting Pi conditions, leading to inhibition of biofilm formation. In fact, PhoB was activated when high polyP levels were maintained in the stationary phase, whereas it remained inactive when the polymer was degraded or absent. PhoB activation was mediated by acetyl phosphate with the consequent repression of biofilm formation owing to the downregulation of c-di-GMP synthesis and the inhibition of autoinducer-2 production. These results allowed us to propose a model showing that PhoB is a component in the signal cascade regulating biofilm formation triggered by fluctuations of polyP levels in E. coli cells during stationary phase.